2016
DOI: 10.1007/s11060-016-2248-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of miRNAs on chromosome 14q32.31 region correlates with tumor aggressiveness and survival of glioblastoma patients

Abstract: The 54 microRNAs (miRNAs) within the DLK-DIO3 genomic region on chromosome 14q32.31 (cluster-14-miRNAs) are organized into sub-clusters 14A and 14B. These miRNAs are downregulated in glioblastomas and might have a tumor suppressive role. Any association between the expression levels of cluster-14-miRNAs with overall survival (OS) is undetermined. We randomly selected miR-433, belonging to sub-cluster 14A and miR-323a-3p and miR-369-3p, belonging to sub-cluster 14B, and assessed their role in glioblastomas in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…At present, the treatment of GBM cells mainly depends on chemotherapy, and the increase of drug resistance is a global problem (4). Several studies have revealed that miRNA is involved in the process of glioma resistance (23)(24)(25). Collectively, the present findings demonstrated that miR-181a-5p is a tumor suppressor gene in GBM, potentially providing a theoretical basis for treatment of drug-resistant GBM in clinical practice.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…At present, the treatment of GBM cells mainly depends on chemotherapy, and the increase of drug resistance is a global problem (4). Several studies have revealed that miRNA is involved in the process of glioma resistance (23)(24)(25). Collectively, the present findings demonstrated that miR-181a-5p is a tumor suppressor gene in GBM, potentially providing a theoretical basis for treatment of drug-resistant GBM in clinical practice.…”
Section: Discussionsupporting
confidence: 51%
“…miRs are endogenous non-coding RNAs that are 20-25 nucleotides in length. Dysregulation of miRNAs in brain tumors result in chromosomal aberration, epigenetic modifications and mutations (25). miRNAs possess special biological characteristics and an important function (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…MGMT Promoter Methylation, and IDH1-R132H mutation testing were performed as previously described [ 22 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, increased expression of miR-411 and -1185 has been involved in the pathogenesis of cardiovascular disease [44,45] and miR-495-3p in tumour sensitivity [46]. Decreased expression of miR-299-3p and -369-3p has been linked to tumorigenesis [47,48] and miR-300 to poor prognosis in patients with cancer [49].…”
Section: Discussionmentioning
confidence: 99%